A discrete-choice experiment to determine patient preferences for injectable multiple sclerosis treatments in Germany. (March 2016) - Poulos, Christine; Kinter, Elizabeth; Yang, Jui-Chen; Bridges, John F. P.; Posner, Joshua; Gleißner, Erika; Mühlbacher, Axel; Kieseier, Bernd
Objectives: The aim of this study was to assess the relative importance of features of a hypothetical injectable disease-modifying treatment for patients with multiple sclerosis using a discrete-choice experiment. Methods: German residents at least 18 years of age with a self-reported physician diagnosis of multiple sclerosis completed a 25–30 minute online discrete-choice experiment. Patients were asked to choose one of two hypothetical injectable treatments for multiple sclerosis, defined by different levels of six attributes (disability progression, the number of relapses in the next 4 years, injection time, frequency of injections, presence of flu-like symptoms, and presence of injection-site reactions). The data were analyzed using a random-parameters logit model. Results: Of 202 adults who completed the survey, results from 189 were used in the analysis. Approximately 50% of all patients reported a diagnosis of relapsing–remitting multiple sclerosis, and 31% reported secondary progressive multiple sclerosis. Approximately 71% of patients had current or prior experience with injectable multiple sclerosis medication. Approximately 53% had experienced flu-like symptoms caused by their medication, and 47% had experienced mild injection-site reactions. At least one significant difference was seen between levels in all attributes, except injection time. The greatest change in relative importance between levels of an attribute was years until symptoms get worse from 1 to 4 years. The magnitude of this difference was about twice that of relapses in the next 4 years, frequency of injections, and flu-like symptoms. Conclusions: Most attributes examined in this experiment had an influence on patient preference. Patients placed a significant value on improvements in the frequency of dosing and disability progression. Results suggest that changes in injection frequency can be as important as changes in efficacy and safety attributes. Understanding which attributes of injectable therapies influence patient preference could potentially improve outcomes and adherence in patients with multiple sclerosis.